Impacts of Foreign Direct Investment on Economic Development: Does Institutional Quality Matter? - Thuy T. Dang; Tran Thi Kim Oanh; Ha Luong Thanh; Trung Ngoc Nguyen (Ital Publication, 2023)
The linkage between foreign direct investment (FDI) and economic development has been demonstrated in economic literature. In this study, we analyze the impact of FDI on economic development, considering the role of institutional quality in 63 provinces/cities in Vietnam in the period 2005–2022. Applying various regression methods, such as Pooled OLS, FEM, REM, GMM, and PVAR, the results confirm that foreign direct investment and institutional quality have a positive impact on economic development. Findings also provide evidence that institutional quality is an important factor in attracting FDI, determining both the quality and quantity of inflows from other countries into Vietnam. Some policy implications are given to promote the role of institutions and attract foreign direct investment, thereby promoting the economic development of provinces and cities in Vietnam. Doi: 10.28991/ESJ-2023-07-06-05 Full Text: PDF